Statical: Evaluation of an open access biostatistics tool. - Pace-Loscos, Tanguy; Gal, Jocelyn; Contu, Sara; Schiappa, Renaud; Chamorey, Emmanuel; Culié, Dorian (Health Informatics Journal)
Background: Statistical analysis is crucial in clinical research, but many clinicians lack training or support. StatiCAL, a free and intuitive tool, was created to address this gap without needing coding skills. This study evaluates its effectiveness and usability by analyzing physicians' performance and perceptions during real-world statistical tasks. Methods: We conducted a cross-sectional study evaluating StatiCAL's usability and effectiveness. Surgical physicians analyzed a clinical dataset using StatiCAL after completing a background questionnaire. Usability was measured with the French SUS, and all analyses were independently verified in R. Results: Fourteen physicians with limited prior experience in statistical analysis participated. All successfully completed the assigned tasks using StatiCAL, with an average completion time of 28 minutes. Interestingly, participants without prior experience completed tasks significantly faster than those with experience (p = 0.044). The average F-SUS score was 85.33, indicating high usability above the standard threshold. Conclusions: StatiCAL showed high usability and effectiveness, allowing clinicians, regardless of prior experience, to perform accurate statistical analyses efficiently. Its intuitive interface supports broader access to biostatistics, encourages collaboration with specialists, and simplifies research workflows. Further studies with larger, more diverse populations are needed to confirm and expand these findings.